2008
DOI: 10.1016/j.jcrs.2008.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Incision sizes before and after implantation of SN60WF intraocular lenses using the Monarch injector system with C and D cartridges

Abstract: With new injector systems and an appropriate docking implantation technique, foldable hydrophobic acrylic IOLs can be implanted through 2.0 mm tunnel incisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…10,11 Maximum incision stretch has been shown to occur during IOL implantation. 11 Steinert and Deacon 12 reported that an irreversible increase in incision size follows phacoemulsification surgery due to initial stretch-related incision tearing.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Maximum incision stretch has been shown to occur during IOL implantation. 11 Steinert and Deacon 12 reported that an irreversible increase in incision size follows phacoemulsification surgery due to initial stretch-related incision tearing.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some disadvantages to B-MICS including wound damage, difficulties in mastering the technique, leakage due to thermal burn and the need for wound enlargement for IOL implantation [2,5,10,28,29] . C-MICS does not have the above-mentioned disadvantages and can therefore be easily and safely performed by most surgeons [28,[30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 4,5,[9][10][11] found wound construction and wound enlargement to be affected by various injector cartridges or insertion methods. Those studies found that the stress to the wound structure was greatest when the IOL passed through the wound.…”
Section: Discussionmentioning
confidence: 99%
“…3 New IOL designs and injector systems have been developed to adapt to the technological changes. Moreover, studies 4,5 have evaluated the relationship between various types of IOLs, injector systems, insertion techniques, and incision sizes. In these systems, an IOL produced from a soft material is tightly rolled and then drawn into the cartridge.…”
mentioning
confidence: 99%